Implant Stability Changes During Early Phase of Healing and Suggested the Fast Time of Loading: A Clinical Trial Study with ITI SLA Implants - AR. Rokn; AAR. Rasouli Ghahroudi; AS. Miremadi; MJ. Kharazi fard; A. Mesgarzadeh (Tehran University of Medical Sciences, 2009)
Objective: To assess the stability changes as a reflection of early healing around roughened- surface implants in human by resonance frequency analysis (RFA). Materials and Methods: One hundred and fifty one ITI SLA implants were placed in either maxilla or mandible of 68 patients. Bone type was classified into 4 groups according to Lekholm and Zarb index. RFA was used for direct implant stability measurement on the day of implant placement, and at 14, 30 and 60 days after placement. Student t-test and ANOVA served for statistical analysis. Results: No early failure occurred. The highest and lowest primary stability was measured in type 1 and type 4 bone, respectively. Implant stability increased over time in types 3 and 4 bone but continuously decreased in type 1 bone during the first 60 days of healing. In type 2 a small decrease in stability was observed until 30 days, and after that the stability increased. The difference between implant stability in type 2 and type 4 bone at each time point was highly significant (P<0.001). Implant stability did not change significantly during the 60-day period in type 2 bone (P>0.05). The effect of implant length and diameter on stability at different times was tested with mixed model ANOVA, and no significant difference among groups was observed (P>0.05) Conclusion: The present study demonstrated that the pattern of stability changes was different among various bone types. With regard to primary stability and pattern of stability changes in types 2 and 3 bone, immediate and early loading protocols can be recommended in these two bone types, respectively.